ضوابط الدراسات البيانية عند عائشة عبد الرحمن: دراسة تحليلية - فارح, ابتسام (University of Eloued جامعة الوادي, 2021)
يهدف هذا المقال إلى رصد مدى تطبيق عائشة عبد الرحمن لضوابط منهج الدرس البياني، من خلال تفسيرها البياني، وكتابها "الإعجاز البياني للقرآن، ومسائل ابن الأزرق". وتظهر أهمية هذا البحث في إثراء المكتبة التفسيرية، وإبراز ضوابط المنهج البياني، كونه منهجا يرمي إلى فهم دقيق محرر للمعجزة الخالدة، وعلى الوجه الذي جاءت به مفرداتها وتراكيبها. وقد تساوق المنهج الاستقرائي، والمنهج التحليلي في نمنمة فُسيفساء هذا البحث. وإجمالا، أكد البحث على اجتهاد عائشة عبد الرحمن في الالتزام بضوابط الدرس البياني والمتمثلة في: دراسة الموضوع الواحد في القرآن، دراسة حول القرآن، دراسة في القرآن. This article aims to identify the extent to which Aisha Abd Arrahman has applied the rules of the statement lesson, approach through her interpretation and book “The Miraculousness statement of the Qur’an and the issues of Ibn al-Azraq”. The importance of this research lies in enriching the interpretive library, and highlighting the rules of the interpretive approach as it is a method aims to understand the timeless miracle accurately, and of the way its vocabulary and compositions have come in. We adopted the exploratory and descriptive approaches in this study. The research emphasized Aisha Abd Araahman’s diligence in adhering to the rules of the Quranic lesson, namely: studying the same subject in the Qur’an, studying the Qur’an, and studying in the Qur’an.